Effectiveness of Individualized Homoeopathic Medicine in LM Potencies in Pediatric Patients: A Single-Group Pretest-Posttest Interventional Study - Vignesh Kumar S.; Shishir Kumar Singh; K. Vijay Ananth; Rajib Purkait; Kumaravel V.; Tapan Kumar Behera (Homœopathic Links, 2026)
Abstract Scabies or seven years itch is a parasitic infestation on skin, by itch mite Sarcoptes scabiei var. hominis. Approximately 30 crore people are annually affected worldwide. In India, the incidence ranges from 18 to 42% in rural and urban areas. This study attempts to know the response of pediatric scabies to individualized homoeopathic medicines by LM potencies. Patients satisfying the criteria for confirmed scabies and clinical scabies in the International Alliance for the Control of Scabies consensus (2018), along with fulfilling the eligibility criteria were enrolled. Individualized homoeopathic medicines (IHMs) in LM potencies were given as intervention and follow-up done on monthly basis for 3 months. Photograph of lesions and the Children Dermatology Life Quality Index (CDLQI) score were taken as the outcomes from baseline and end of 3 months. Changes in photographs were examined under the blind consensus method by the head of the pediatric department and the corresponding author. The Modified Naranjo Criteria for Homeopathy (MONARCH) scoring was done for evaluating the causal relationship between outcome and intervention. Fifty cases were enrolled for the study, and 45 patients completed the study. Thirty-seven patients showed improvement in photography, examined by blinded consensus with kappa Cohen's of 0.80 (substantial agreement). The CDLQI score (n = 45) (t 38.59: p < 0.001) show significant difference statistically. Eleven remedies including Sulphur and Mercurius sol from potencies LM1 to LM5 were used in the study. Conclusion The study suggests IHMs in LM potencies having positive response in treating scabies. This study is useful for framing hypothesis in future studies with vigorous design. Trial registered in Clinical Trials Registry of India on 16/04/2024 Ref. no- CTRI/2024/04/5767.